Cyclic Stress Response and Fracture Behaviors of Alloy 617 Base Metal and Weld Joints under LCF Loading - Seon Jin Kim; Rando Tungga Dewa; Woo Gon Kim; Min Hwan Kim (Advances in Materials Science and Engineering)
Cyclic stress response and fracture behaviors of Alloy 617 base metal (BM) and Alloy 617 weld joints (WJ) are investigated under strain controlled low cycle fatigue (LCF) loading. Axial fully reversed total-strain controlled tests have been conducted at room temperature with total strain ranges of 0.6, 0.9, 1.2, and 1.5%. At the all testing conditions, weld joint specimens have shown higher peak stresses than the base metal specimens, whereas the plastic strain accumulation of the base metal specimens is comparatively higher than those of the weld joint specimens. The cyclic stress response behavior of both base metal and weld joint specimens revealed initial cyclic hardening during first small number of cycles followed by progressive softening to failure. Higher strain amplitudes decreased the fatigue lives for both base metal and weld joint specimens; subsequently weld joint specimens had lower fatigue resistances relative to base metal specimens. Furthermore, the cracking in weld joint specimens initiated in the weld metal (WM) region. The crack initiation and propagation showed transgranular mode for both base metal and weld joint specimens; especially weld joint specimens showed a wedge type crack initiation about 45 degrees to the loading direction because of the dendritic structure.